On the relationship of texts, images and illustrations in the construction of subject positions using the example of the (conscious) consumer - Brandmayr, Michael (Momentum Quarterly, 2020)
This contribution uses an example to show how the subject positions of the "conscious consumer" are constituted in graphics and images and conveyed to the viewer. For this purpose, the image "your personal slaves" by Daniel Garcia will be analyzed with the three step method according to Panofsky. The iconological content of the image is interpreted in the main part of the text. The thesis here is that even in the current accentuation of conscious consumption practices, the function of consumption, already noticed in Veblen's work, namely to produce discourse, can be demonstrated. Not only does the focus on a sustainable, conscious mode of consumption correspond more closely to the consumption practice of middle and upper classes and their financial possibilities; the positioning of this practice as morally superior and objectively reasonable provides reasons to classify deviant behaviour as backward and to devalue it. Based on this example, the last part of the article will discuss two theses that argue that images have a certain uniqueness in the construction of subjectivity compared to texts.
Keywords: subjectification; image analysis; classism; consumption